Effect of Metformin Intervention during Pregnancy on the Gestational Diabetes Mellitus in Women with Polycystic Ovary Syndrome: A Systematic Review and Meta-Analysis - Zhihong Zhuo; Aiming Wang; Huimin Yu (Journal of Diabetes Research)
Metformin is an effective insulin sensitizer treating type 2 diabetes mellitus. However, the functional consequences of metformin administration throughout pregnancy on gestational diabetes mellitus (GDM) with polycystic ovary syndrome (PCOS) have not been assessed. We therefore performed a meta-analysis and system review to determine the effect of metformin on GDM in PCOS. A meta-analysis was performed on the published studies before December, 2013. Meta-analysis examined whether metformin could reduce GDM occurrence in PCOS with a fixed effect model. The odds ratio (OR) with 95% confidence interval (95% CI) was calculated to estimate the strength of association. A total of 13 studies including 5 RCTs and 8 non-RCTs were enrolled. Ultimately, effectiveness analysis demonstrated that, in total, there was no significant availability of metformin on GDM in PCOS in contrast to placebo (OR = 1.07, 95% CI 0.60–1.92) in RCTs and significant availability of metformin on GDM (OR = 0.19, 95% CI 0.13–0.27) was indicated in non-RCTs. In summary, according to the results of our meta-analysis, strictly, metformin did not significantly effect on GDM with PCOS, though more multicenters RCTs still need to be investigated.